Comparison of biosimilar filgrastim with a reference product: pharmacokinetics, pharmacodynamics, and safety profiles in healthy volunteers - Choi C; Yoo BW; Kim CO; Hong T; Jin BH; Seo KS; Jang JY; Park MS (Dove Medical Press, 2018)
Chungam Choi,1 Byung Won Yoo,2 Choon Ok Kim,2 Taegon Hong,2 Byung Hak Jin,2 Kwang-Seok Seo,3 Ja Yun Jang,4 Min Soo Park2 1Department of Nuclear Medicine, Severance Hospital, Yonsei University Health System, Seoul, Republic of Korea; 2Department of Clinical Pharmacology, Severance Hospital, Yonsei University Health System, Seoul, Republic of Korea; 3Biopharmaceutical Research Laboratories, Dong-A Socio R&D Center, Yongin-si, Republic of Korea; 4Product Development Division, Dong-A ST Co., Ltd, Seoul, Republic of Korea Purpose: Filgrastim, a granulocyte-colony stimulating factor, is used to treat patients with neutropenia, including neutropenic fever. Leucostim® is a recombinant filgrastim product tested for biosimilarity with its reference product, Neupogen®. We conducted a comparative clinical trial of the 2 products. Patients and methods: A randomized, open-label, 2-way crossover, single-dose Phase I study was conducted for 56 healthy subjects. After a 5 and 10 μg/kg single subcutaneous administration of test and reference product, pharmacokinetic and pharmacodynamic parameters (absolute neutrophil count and CD34+ cell count) were compared. During the study, safety tests and adverse event monitoring were performed. Results: The test and the reference products had a comparable pharmacokinetic, pharmacodynamic, and safety profile. In both 5 and 10 μg/kg dosing, the 90% CIs of the test to reference ratio for primary parameters (peak plasma concentration and area under the plasma concentration vs time curve from time 0 extrapolated to the infinite time for plasma filgrastim concentration; maximal effect and area under the time-effect curve from time 0 to time of the last quantifiable effect for absolute neutrophil count) were within the 0.8–1.25 range. In addition, safety profiles between the 2 products were similar without any serious adverse events. Conclusion: This study has provided firm clinical evidence that the test filgrastim product is similar to its reference filgrastim product. Keywords: bioequivalence, biosimilar, G-CSF, biologics